Investigation into efficiency of adsorption process during utilization of curing gases in tyre production - Vlasov, Gennady; Syritsyn, Leonid; Tchemerinski, Vyacheslav; Zhakomin, Nikolai (Journal of Environmental Engineering and Landscape Management, 2005)
The problem considered in the paper is mathematical and physical modeling of the adsorption process during utilization of gas emissions of cured tyres and tyre components. The paper contains synthesis and analysis of mathematical models for violent and moderate gassing. It describes an adsorption scheme, formulates an experimental dependence of productivity upon the concentration of emissions in an absorber chamber of a system used for trapping of curing gas emissions and vapors. Absorbcijos proceso, utilizuojant padangų gamybos metu susidariusias vulkanizacijos dujas, efektyvumo tyrimai Santrauka. Nagrinėjamas adsorbcijos proceso, utilizuojant vulkanizuotų padangų bei jų komponentų gamybos metu susidariusias dujas, matematinis bei fizinis modeliavimas. Pateikiama intensyvaus bei nežymaus dujų išsiskyrimo matematinių modelių sintezė bei analizė. Aprašyta adsorbcijos schema, formulėmis išreikšta eksperimentiniu būdu nustatyta produktyvumo priklausomybė nuo emisių koncentracijos vulkanizacijos dujų emisijų ir garų sugaudymo sistemos absorbcinėje kameroje. Reikšminiai žodžiai: padangos, vulkanizacijos dujos, lakieji junginiai, utilizacija, adsorbcijos procesas. First Published Online: 14 Oct 2010